Effect of Glycyrrhiza uralensis extract, Lactobacillus acidophilus and their combined supplementation on production performance, immunity, antioxidation and intestinal health in broilers - Lu, JianXiong; Li, ShuaiBing; Wu, JiaHui; Chen, Yan; Jiang, SuSu; Zhang, GuoHua (Frontiers in Veterinary Science, 2025)
This study investigated the effects of Glycyrrhiza uralensis extract (GUE), Lactobacillus acidophilus (Lac), and their combination on production performance, immune and antioxidant functions, and intestinal health in broilers. A total of 420 one-day-old male Liangfenghua broilers were randomly assigned to four groups and fed with basal diet, GUE diet with 0.1% GUE, Lac diet with 4.5 × 10⁷ CFU/kg Lac, or GUE+Lac diet with 0.1% GUE and 4.5 × 10⁷ CFU/kg Lac. The experiment lasted 84 days. The results demonstrated that both GUE and Lac enhanced health by increasing immune organ indices, serum levels of IFN-γ, IL-2, IgA, and IgG, and activities of GSH-Px and SOD (p < 0.05). They also improved intestinal morphology and barrier function by increasing villus height and the villus height to crypt depth ratio (VH/CD), upregulating expression of Zonula occludens-1 (ZO-1), mucin-2 (MUC2), and Occludin (OCLN), and reducing expression of IL-1β, TLR4, and TNF-α (p < 0.05), which increased nutrient metabolic rates (p < 0.05). These changes ultimately resulted in improved production performance, evidenced by increased body weight and decreased abdominal fat rate (p < 0.05). Notably, the combined GUE+Lac exhibited positive synergistic effects, leading to enhanced immune function as shown by increased serum levels of IL-2, IFN-γ, IgA, and IgG; improved antioxidant capacity indicated by elevated GSH-Px activity in serum and liver; and enhanced intestinal morphology and barrier function by increased villus height and VH/CD ratio, upregulated expression of ZO-1, MUC2, and OCLN, and reduced expression of IL-1β and TLR4, TNF-α (p < 0.05) compared to both GUE and Lac alone. This synergism between GUE and Lac significantly increased body weight and nutrient metabolic rates while decreasing abdominal fat rate in broilers. Altogether, we demonstrated the synergistic enhancement of production performance, immunity, antioxidation and intestinal health in broilers by combining GUE and Lactobacillus acidophilus. These findings provide robust scientific support for the future development and application of feed additive.